Lithium ion battery and preparation method thereof
By using a combination of micron-sized silicon materials and a specific non-aqueous electrolyte, the problem of volume expansion of silicon-based materials during charging and discharging has been solved, resulting in lithium-ion batteries with high energy density and high capacity retention, and improving the cycle performance and safety performance of the batteries.
Patent Information
- Application Number
- CN202410488247.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-22
- Publication Date
- 2025-10-24
AI Technical Summary
Among existing lithium-ion battery anode materials, silicon-based materials suffer structural damage due to volume expansion during charging and discharging, affecting battery cycle performance and safety. Nano-silicon materials have low initial efficiency and are difficult to industrialize, and the electrolyte is prone to gas generation, making it difficult to achieve high energy density.
Micron-sized silicon material is used as the negative electrode active material, with a silicon content of more than 80% by weight. Combined with a specific non-aqueous electrolyte containing more than 10% by weight of fluoroethylene carbonate, a stable SEI film is formed through two-stage charging and discharging treatment to suppress the volume change of silicon.
Significantly improves the energy density and capacity retention of lithium-ion batteries, and enhances battery cycle performance and safety.
Smart Images

Figure SMS_1
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of lithium ion batteries, in particular to a high energy density lithium ion battery and a preparation method thereof. BACKGROUND
[0002] Lithium ion batteries have been widely used in various fields such as consumer electronics, electric tools, electric vehicles, etc. With the development of society, higher requirements for the energy density of lithium ion batteries are constantly put forward.
[0003] At present, the commercialized negative electrode material of lithium battery is still mainly graphite, but its theoretical specific capacity is low. If the energy density of power battery is to be further improved, it is necessary to develop new high-capacity negative electrode materials.
[0004] Silicon negative electrode material has the advantage of ultra-high capacity, however, the structural unit of silicon expands and shrinks by 300% during charging and discharging, which easily leads to cracks and pulverization of silicon-containing negative electrode material particles, causing the silicon material to lose electrochemical activity. Meanwhile, the cracks and new fracture surfaces caused by volume change will come into contact with the electrolyte and form an unstable SEI film. The SEI protective layer continuously breaks and exposes the fresh silicon surface to the electrolyte, thus continuously consuming the electrolyte to generate a new SEI film, which adversely affects the cycle performance of the battery. In the prior art, nano-sized silicon negative electrode materials are usually used, but nano-silicon has a small size and a large specific surface area, and has a nano effect. Therefore, the initial efficiency of the nano-silicon negative electrode is low, and the specific capacity cannot exceed 3000 mAh / g. Moreover, the nano-scale homogenate coating process is difficult to implement industrialization. The industry generally improves the above-mentioned problems of nano-silicon material by silicon-carbon compounding, but the addition of a large amount of carbon reduces the high capacity of silicon. Therefore, it is necessary to solve the expansion problem of silicon and continuously optimize the material. At the same time, it is very important to develop an electrolyte suitable for high energy density batteries to solve the problems of easy gas generation and silicon negative electrode expansion and destruction of the negative electrode SEI film in the current high energy density batteries, further improve the cycle performance and safety performance of the battery. In order to improve the energy density of lithium batteries, it is necessary to continuously develop combinations of high specific energy battery materials and optimize the design of the battery cell. SUMMARY
[0005] To solve the problems in the prior art, the inventors of the present application propose to use micron-sized silicon material as the negative electrode active material. However, micron-sized silicon has a large particle size, and therefore is severely pulverized during charging and discharging, which causes the particles to lose electrical connection and leads to rapid capacity decay. A general pure silicon electrode cannot achieve the high specific capacity of micron-sized silicon.
[0006] The inventors of the present application have found that, when the negative active material is a micrometer silicon material, the content of silicon in the negative material is 80% by weight or more, and the compaction density of the negative electrode is 1.1-1.7 g / cm 3 , the non-aqueous electrolyte contains a lithium salt and an organic solvent, and the organic solvent contains fluoroethylene carbonate, the content of the fluoroethylene carbonate in the non-aqueous electrolyte is 10% by weight or more, the energy density of the lithium ion battery can be significantly improved, thereby completing the present application.
[0007] The present application aims to provide a high-energy-density lithium ion battery and a preparation method thereof. The lithium ion battery of the present application has high energy density and high capacity retention rate.
[0008] To achieve the above-mentioned purpose, the present application provides a lithium ion battery, wherein the lithium ion battery comprises a positive electrode, a negative electrode, a separator between the positive electrode and the negative electrode, and a non-aqueous electrolyte, the negative electrode comprises a negative electrode current collector and a negative electrode material, the negative electrode material comprises a negative active material, a first binder and a first conductive agent, the negative active material comprises a micrometer silicon material, and the content of silicon in the negative electrode material is 80% by weight or more, the compaction density of the negative electrode is 1.1-1.7 g / cm 3 , the non-aqueous electrolyte contains a lithium salt and an organic solvent, and the organic solvent contains fluoroethylene carbonate, the content of the fluoroethylene carbonate in the non-aqueous electrolyte is 10% by weight or more.
[0009] Preferably, the negative active material comprises a micrometer silicon material and graphite.
[0010] Preferably, the content of silicon in the negative electrode material is 80-95% by weight, the content of graphite is 0-20% by weight, the content of the first binder is 2-6% by weight, and the content of the first conductive agent is 0.05-4% by weight.
[0011] Preferably, the single-sided area density of the negative electrode is 20-50 g / m 2 .
[0012] Preferably, the first binder is one or more of polyacrylonitrile, polytetrafluoroethylene, sodium carboxymethyl cellulose, butadiene styrene rubber and polyacrylic acid.
[0013] Preferably, the first conductive agent is one or more of single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene and graphyne.
[0014] Preferably, the positive electrode comprises a positive electrode current collector and a positive electrode material, the positive electrode material comprises a positive active material, a second binder and a second conductive agent.
[0015] Preferably, in the positive electrode material, the content of the positive electrode active material is 92-98% by weight, the content of the second binder is 1-4% by weight, and the content of the second conductive agent is 1-4% by weight.
[0016] Preferably, the single-sided area density of the positive electrode is 300-400 g / m 2 , and the compacted density of the positive electrode is 3.4-3.8 g / cm 3 .
[0017] Preferably, the second binder is one or more of polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polydifluoroethylene, a polymer containing an oxirane, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, butadiene styrene rubber, acrylated butadiene styrene rubber, epoxy resin, and nylon.
[0018] Preferably, the second conductive agent is one or more of conductive graphite, acetylene black, conductive carbon black, graphene, carbon fiber, carbon nanotube, and ketjen black.
[0019] Preferably, the positive electrode active material is an 8-series nickel-cobalt-manganese ternary material and / or a 9-series nickel-cobalt-manganese ternary material.
[0020] Preferably, the compacted density of the negative electrode is 1.1-1.5 g / cm 3 .
[0021] Preferably, the D50 of the micrometer silicon material is 0.5-20 μm.
[0022] Preferably, the lithium salt is one or more of LiPF6, LiBF4, LiBOB, LiODFB, LiFSI, LiTFSI, and LiPO2F2.
[0023] Preferably, the organic solvent further contains one or more of ethylene carbonate, methyl ethyl carbonate, diethyl carbonate, and dimethyl carbonate.
[0024] Preferably, the content of the lithium salt in the non-aqueous electrolyte is 1.0-1.5 mol / L.
[0025] According to a second aspect of the present application, a preparation method of the lithium ion battery of the first aspect of the present application is provided, which comprises the following steps,
[0026] 1) After the injection of the battery cell, the battery cell is placed and vacuumized for sealing;
[0027] 2) The sealed battery cell is subjected to two-stage charging;
[0028] 3) discharging the charged battery cell to 15-25% SOC;
[0029] 4) vacuumizing the discharged battery cell, and performing the second sealing,
[0030] The two-stage charging includes: a first stage charging at a constant current of 0.2C to 60-70% SOC, and a second stage charging at a constant current of 0.1C to 100% SOC.
[0031] Preferably, the standing condition includes: a standing temperature of 25-40℃, and a standing time of 24-48h.
[0032] Preferably, the two-stage charging is performed at a pressure of 1-2Mpa and a temperature of 40-50℃.
[0033] Preferably, the discharging is performed at a pressure of 1-2Mpa and a temperature of 40-50℃.
[0034] By the above technical solution, the application can provide a high-energy-density lithium ion battery by using a silicon negative electrode and a specific non-aqueous electrolyte, and has excellent effects of improving energy density and capacity retention. DETAILED DESCRIPTION
[0035] The endpoints of the ranges and any values disclosed herein are not limited to the precise values recited as the exact dimensions are not critical to the application. Any numerical value, however, can include values up to and including the value of the lower limit, and values up to and including the value of the upper limit, of the range. The endpoints of the ranges and any values disclosed herein are not limited to the precise values recited as the exact dimensions are not critical to the application. Any numerical value, however, can include values up to and including the value of the lower limit, and values up to and including the value of the upper limit, of the range. The ranges and / or numerical values include endpoints unless specifically excluded. Any reference to the use of a particular value includes use of the value and use of any value up to and including that particular value.
[0036] In one aspect, the application provides a lithium ion battery, wherein the lithium ion battery comprises a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and a non-aqueous electrolyte, the negative electrode comprises a negative electrode current collector and a negative electrode material, the negative electrode material comprises a negative electrode active material, a first binder, and a first conductive agent, the negative electrode active material comprises a micrometer silicon material, and the content of silicon in the negative electrode material is 80% by weight or more, the compaction density of the negative electrode is 1.1-1.7 g / cm 3 The non-aqueous electrolyte contains a lithium salt and an organic solvent, and the organic solvent contains fluoroethylene carbonate, and the content of the fluoroethylene carbonate in the non-aqueous electrolyte is 10% by weight or more.
[0037] According to the application, the negative electrode comprises a first current collector and a negative electrode material coated on the first current collector, and the negative electrode material contains the negative electrode active material, the first binder, and the first conductive agent.
[0038] According to the present application, preferably, the content of silicon in the negative electrode material is 80 to 95% by weight; more preferably, the content of silicon in the negative electrode material is 90 to 95% by weight. By having the negative electrode active material include a micro-silicon material and the content of silicon in the negative electrode material within the above range, in combination with the compaction density thereof and the specific electrolyte of the present application, an excellent effect of significantly improving the energy density and improving the capacity retention rate can be obtained.
[0039] As a specific example of the content of silicon in the negative electrode material, for example, 80% by weight, 81% by weight, 82% by weight, 83% by weight, 84% by weight, 85% by weight, 86% by weight, 87% by weight, 88% by weight, 89% by weight, 90% by weight, 89% by weight, 91% by weight, 92.5% by weight, 93% by weight, 93.5% by weight, 94% by weight, 94.5% by weight, 95% by weight, and the like, and a range formed by any two of the above values can be given.
[0040] According to the present application, preferably, the negative electrode active material includes a micro-silicon material and graphite.
[0041] Preferably, in the negative electrode material, the content of the negative electrode active material is 90 to 95% by weight, the content of the first binder is 2 to 6% by weight, and the content of the first conductive agent is 0.05 to 4% by weight; further preferably, the content of the negative electrode active material is 93 to 95% by weight, the content of the first binder is 3 to 6% by weight, and the content of the first conductive agent is 0.05 to 2% by weight.
[0042] In one preferred embodiment of the present application, the content of silicon in the negative electrode material is 80 to 95% by weight, the content of graphite is 0 to 20% by weight, the content of the first binder is 2 to 6% by weight, and the content of the first conductive agent is 0.05 to 4% by weight.
[0043] As a specific example of the content of the negative electrode active material, for example, 90% by weight, 89% by weight, 91% by weight, 92.5% by weight, 93% by weight, 93.5% by weight, 94% by weight, 94.5% by weight, 95% by weight, and the like, and a range formed by any two of the above values can be given.
[0044] As a specific example of the content of the first binder, for example, 2% by weight, 2.5% by weight, 3% by weight, 3.5% by weight, 4% by weight, 5.5% by weight, 5% by weight, 5.5% by weight, 6% by weight, and the like, and a range formed by any two of the above values can be given.
[0045] As specific examples of the content of the first conductive agent, for example, 0.05% by weight, 0.1% by weight, 0.5% by weight, 1% by weight, 1.5% by weight, 2% by weight, 2.5% by weight, 3% by weight, 3.5% by weight, 4% by weight, and the like, and a range formed by any two of the above values can be given.
[0046] According to the present application, preferably, the single surface area density of the negative electrode is 20-50 g / m 2 ; more preferably, the single surface area density of the negative electrode is 30-40 g / m 2 . By making the single surface area density of the negative electrode within the above range, an excellent effect of increasing the energy density and increasing the capacity retention rate is obtained.
[0047] According to the present application, the first current collector can use various current collectors generally used in the art. Preferably, the current collector is a copper foil current collector. The thickness of the first current collector can be a conventional thickness in the art, preferably, the thickness of the first current collector is 6-8 μm.
[0048] According to the present application, the first binder in the negative electrode material can be selected from various binders commonly used in the art without particular limitation. For example, one or more of polyacrylonitrile, polytetrafluoroethylene, sodium carboxymethyl cellulose, styrene butadiene rubber, and polyacrylic acid; preferably, the binder is a combination of polyacrylic acid, sodium carboxymethyl cellulose, and styrene butadiene rubber.
[0049] In the present application, the content of the first binder in the negative electrode material can be a conventional content generally used in the art for preparing the negative electrode material without particular limitation, preferably, the content of the first binder is 2-6% by weight of the total weight of the negative electrode material. By limiting the content of the first binder within the above range, an excellent effect of effectively suppressing the expansion of silicon and improving the dropping is obtained.
[0050] According to the present application, the first conductive agent in the negative electrode material can be selected from various conductive agents commonly used in the art without particular limitation. For example, one or more of single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, and graphyne.
[0051] In the present application, the content of the first conductive agent in the negative electrode material can be a conventional content generally used in the art for preparing the positive electrode material without particular limitation, preferably, the content of the first conductive agent is 0.05-4% by weight of the total weight of the negative electrode material. By limiting the content of the first conductive agent within the above range, the conductive capacity of the negative electrode material can be effectively improved.
[0052] In the present application, preferably, the compaction density of the negative electrode is 1.1-1.5 g / cm 3; more preferably, the compact density of the negative electrode is 1.2 to 1.4 g / cm 3 By making the negative electrode active material a micro-silicon material, and the content of silicon in the negative electrode within the above range, the compact density of the negative electrode within the above range, in combination with the specific electrolyte of the present application, the energy density can be significantly improved and the capacity retention rate can be improved.
[0053] As a specific example of the compact density of the negative electrode, for example, 1.1 g / cm 3 , 1.15 g / cm 3 , 1.2 g / cm 3 , 1.25 g / cm 3 , 1.3 g / cm 3 , 1.35 g / cm 3 , 1.4 g / cm 3 , 1.45 g / cm 3 , 1.5 g / cm 3 , 1.55 g / cm 3 , 1.6 g / cm 3 , 1.65 g / cm 3 , 1.7 g / cm 3 , and the range formed by any two of the above values.
[0054] According to the present application, preferably, the D50 of the micro-silicon material is 0.5 to 20 μm; more preferably, the D50 of the micro-silicon material is 10 to 20 μm. By making the D50 of the micro-silicon material within the above range, the micro-silicon particles and the conductive agent are cross-linked during the mixing process, forming a network structure that binds the silicon particles, achieving the effect of inhibiting expansion.
[0055] In the present application, the preparation of the lithium ion battery negative electrode can be carried out according to the conventional method for preparing lithium ion battery negative electrodes in the art, without particular limitation. For example, the negative electrode active material can be mixed with the first conductive agent and the first binder, etc., and the mixture can be dispersed in a solvent to prepare a negative electrode slurry, and then the obtained negative electrode slurry can be coated on a first current collector and subjected to drying, calendering, etc.
[0056] According to the present application, the positive electrode comprises a second current collector and a positive electrode material coated on the second current collector, and the positive electrode material contains the positive electrode active material, a second binder and a second conductive agent.
[0057] Preferably, in the positive electrode material, the content of the positive electrode active material is 92-98% by weight, the content of the second binder is 1-4% by weight, and the content of the second conductive agent is 1-4% by weight; more preferably, the content of the positive electrode active material is 94-96% by weight, the content of the second binder is 2-3% by weight, and the content of the second conductive agent is 1-2% by weight.
[0058] According to the present application, preferably, the positive electrode active material is an 8-series nickel-cobalt-manganese ternary material and / or a 9-series nickel-cobalt-manganese ternary material. The 8-series nickel-cobalt-manganese ternary material refers to a nickel-cobalt-manganese ternary material with a nickel element molar content greater than or equal to 80%, and the 9-series nickel-cobalt-manganese ternary material refers to a nickel-cobalt-manganese ternary material with a nickel element molar content greater than or equal to 90%.
[0059] As a specific example of the content of the positive electrode active material, for example, 92% by weight, 93% by weight, 93.5% by weight, 94% by weight, 94.5% by weight, 95% by weight, 95.5% by weight, 96% by weight, 96.5% by weight, 97% by weight, 97.5% by weight, 98% by weight, etc., and a range formed by any two of the above values can be given.
[0060] As a specific example of the content of the second binder, for example, 1% by weight, 1.5% by weight, 2% by weight, 2.5% by weight, 3% by weight, 3.5% by weight, 4% by weight, etc., and a range formed by any two of the above values can be given.
[0061] As a specific example of the content of the second conductive agent, for example, 1% by weight, 1.5% by weight, 2% by weight, 2.5% by weight, 3% by weight, 3.5% by weight, 4% by weight, etc., and a range formed by any two of the above values can be given.
[0062] According to the present application, preferably, the single surface area density of the positive electrode is 300-400 g / m 2 ; more preferably, the single surface area density of the positive electrode is 320-360 g / m 2 .
[0063] According to the present application, preferably, the compacted density of the positive electrode is 3.4-3.8 g / cm 3 ; more preferably, the compacted density of the positive electrode is 3.5-3.7 g / cm 3 .
[0064] The present application controls the compacted density of the positive electrode to be at its limit compacted density, and the single surface area density to be 300-400 g / m 2, while matching the compaction density and thickness of the negative electrode, effectively improving the capacity and energy density of the lithium-ion battery, reducing the internal resistance and polarization loss of the battery, while ensuring the insertion and extraction of lithium ions, and extending the cycle life of the battery.
[0065] According to the present invention, the second current collector can use any of the various current collectors commonly used in the art. Preferably, the current collector is an aluminum foil current collector; more preferably, the second current collector is a carbon-coated aluminum foil current collector. The thickness of the aluminum foil current collector can be a conventional thickness for aluminum foil current collectors in the art, preferably, a thickness of 6-20 μm.
[0066] According to the present invention, the thickness of the carbon layer in the carbon-coated aluminum foil current collector may also be the conventional thickness of the carbon layer in the carbon-coated aluminum foil current collector in the art. Preferably, the thickness of the carbon layer on the carbon-coated current collector is 1-5 μm.
[0067] In the present invention, the carbon in the carbon layer of the carbon-coated aluminum foil current collector can come from various materials commonly used in the art to prepare carbon-coated aluminum foil current collectors, without special restrictions. For example, the carbon in the carbon layer comes from one or more of carbon black materials, conductive graphite materials, vapor-grown carbon fibers, carbon nanotubes, and graphene.
[0068] According to the present invention, the second binder in the positive electrode material can be selected from various binders commonly used in the art, without particular limitation. For example, it can be one or more of polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinylidene fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, and nylon. Preferably, the binder is polyvinylidene fluoride.
[0069] In the present invention, the content of the second binder in the positive electrode material can be any conventional content commonly used in the art for preparing positive electrode materials, without particular limitation. Preferably, the content of the binder is 1-3% by weight of the total weight of the positive electrode material. By limiting the binder content to the above range, the binding properties of the positive electrode material can be effectively improved, which is beneficial for enhancing the performance of lithium-ion batteries.
[0070] According to the present invention, the second conductive agent in the positive electrode material can be selected from various conductive agents commonly used in the art, without particular limitation. For example, it can be one or more of conductive graphite, acetylene black, conductive carbon black, graphene, carbon fiber, carbon nanotubes, and Ketjen black. Preferably, the second conductive agent is conductive carbon black.
[0071] In the present application, the content of the second conductive agent in the positive electrode material can be the conventional content generally used in the art for preparing the positive electrode material, and is not particularly limited, preferably, the content of the second conductive agent is 1-3% by weight of the total weight of the positive electrode material. By limiting the content of the conductive agent in the above range, the conductivity of the positive electrode material can be effectively improved.
[0072] In the present application, when the lithium ion battery positive electrode material is used to prepare a lithium ion battery positive electrode, preferably, the lithium ion battery positive electrode material is dispersed in a solvent to obtain a positive electrode slurry, and then the obtained positive electrode slurry is coated on a current collector by a conventional coating method in the art, and after drying and calendering and other conventional treatments, a lithium ion battery positive electrode is obtained.
[0073] According to the present application, the non-aqueous electrolyte contains an organic solvent and a lithium salt, the organic solvent contains fluoroethylene carbonate (FEC), and the content of the fluoroethylene carbonate in the non-aqueous electrolyte is 10% by weight or more; preferably, the content of the fluoroethylene carbonate in the non-aqueous electrolyte is 15-30% by weight.
[0074] In the present application, by using fluoroethylene carbonate solvent, fluoroethylene carbonate solvent forms a thin and stable SEI film on the negative electrode surface before carbonate solvent, inhibits the decomposition of carbonate solvent and the oxidation of silicon negative electrode, and the product has good flexibility and buffering effect on the volume expansion of silicon negative electrode.
[0075] In the present application, the organic solvent can also contain one or more of vinyl carbonate, methyl ethyl carbonate, diethyl carbonate and dimethyl carbonate.
[0076] In the present application, the lithium salt can be various lithium salts generally used in the art for preparing lithium ion batteries, and is not particularly limited, for example, one or more of LiPF6, LiBF4, LiPO2F2, LiTFSI, LiBOB, LiDFOB, LiFSI, LiTFSI, LiSbF6, LiAsF6, LiN(SO2CF3)2, LiC(SO2CF3)3 and LiN(SO2F)2 can be selected. In the present application, preferably, the lithium salt is one or more of LiPF6, LiBF4, LiBOB, LiODFB, LiFSI, LiTFSI and LiPO2F2; more preferably, the lithium salt is LiPF6.
[0077] In the present application, the content of the lithium salt can be the content commonly used in the lithium ion battery non-aqueous electrolyte in the art, and is not particularly limited. For example, the content of the lithium salt in the lithium ion battery non-aqueous electrolyte can be 1-1.5 mol / L; preferably, the content of the lithium salt in the lithium ion battery non-aqueous electrolyte is 1.1-1.3 mol / L. When the content of the lithium salt is within this range, not only good battery performance can be achieved, but also the electrolyte cost can be effectively controlled.
[0078] According to the present application, the separator placed between the positive electrode and the negative electrode can be various materials commonly used as separators in the art, and is not particularly limited, for example, can be one of polyolefin-based separators, polyamide-based separators, polysulfone-based separators, polyphosphazene-based separators, polyether sulfone-based separators, polyether ether ketone-based separators, polyether amide-based separators and polyacrylonitrile-based separators.
[0079] According to the second aspect of the present application, a preparation method of the lithium ion battery of the first aspect of the present application is provided, which comprises the following steps,
[0080] 1) After the injection of the cell, the cell is placed, and then the cell is vacuumized and sealed;
[0081] 2) The sealed cell is subjected to two-stage charging;
[0082] 3) The charged cell is discharged to 15-25% SOC;
[0083] 4) The discharged cell is vacuumized and sealed,
[0084] Among them, the two-stage charging includes: the first stage charging of constant current charging to 60-70% SOC at 0.2C current, and the second stage charging of constant current charging to 100% SOC at 0.1C current.
[0085] In the present application, the cell after injection is placed for the purpose of electrolyte infiltration, and the conditions of the placement can achieve the above purpose, for example, the conditions of the placement can include: the temperature of the placement is 25-40℃, and the time of the placement is 24-48h;
[0086] According to the present application, preferably, the two-stage charging is carried out at a pressure of 1-2Mpa and a temperature of 40-50℃; more preferably, the two-stage charging is carried out at a pressure of 1.5-1.9Mpa and a temperature of 40-50℃. By carrying out the two-stage charging under the above conditions, the compactness, stability and consistency of the SEI film can be improved, thereby inhibiting the expansion of the silicon-carbon negative electrode material during the cycle process and improving the cycle performance of the battery.
[0087] According to the application, preferably, the discharging is carried out at a pressure of 1-2 MPa and a temperature of 40-50 DEG C; more preferably, the discharging is carried out at a pressure of 1.5-1.9 MPa and a temperature of 40-50 DEG C.
[0088] The application will be described in detail below by way of examples, but the application is not limited to the following examples.
[0089] In the following examples and comparative examples, the materials used are all commercially available unless otherwise specified.
[0090] Example 1
[0091] The positive electrode tab is coated with a positive electrode material, and the positive electrode material is composed of the following components in mass percentage: LiNi 0.8 Co 0.1 Mn 0.1 O2 96%, polyvinylidene fluoride 3%, conductive carbon black 1%, and the compaction density of the positive electrode tab is 3.6 g / cm 3 , and the surface density is 300 g / m 2 .
[0092] The negative electrode tab is coated with a negative electrode active material, and the negative electrode active material is composed of the following components in mass percentage: micron silicon (D50 of micron silicon is 15 pm) 93%, conductive carbon black 0.5%, single-walled carbon nanotubes 0.2%, graphene conductive agent 0.05%, butyl rubber 1%, carboxymethyl cellulose 1.25%, polyacrylic acid binder 4%, and the compaction density of the negative electrode tab is 1.3 g / cm 3 , and the surface density is 30 g / m 2 .
[0093] The electrolyte is a 1.2 mol / L lithium hexafluorophosphate carbonate electrolyte, and the carbonate organic solvent is a mixed solvent obtained by mixing in proportion (the specific mass ratio is DEC:EMC:EC=3:5:2), and the proportion of fluoroethylene carbonate in the electrolyte is 10% by weight.
[0094] The separator is a polyolefin separator.
[0095] The preparation method of the battery cell is as follows.
[0096] 1) After the battery cell is injected with liquid, the battery cell is placed and vacuumized for one sealing;
[0097] 2) The battery cell after one sealing is subjected to two-stage charging;
[0098] 3) The battery cell after charging is discharged to 20% SOC;
[0099] 4) The battery cell after discharging is vacuumized for two sealing,
[0100] The standing temperature is 25°C, and the standing time is 24 hours.
[0101] The two-stage charging and discharging is performed at a pressure of 1.6 MPa and a temperature of 40°C.
[0102] The two-stage charging includes: first-stage charging: constant current charging at 0.2C to 70%; and second-stage charging: constant current charging at 0.1C to a voltage of 100% SOC.
[0103] The obtained lithium ion battery is measured according to the following method, and the measurement results and the preparation conditions are shown in Table 1.
[0104] The energy density is measured as follows: after the two sealing is completed, the battery is charged and discharged at 0.33C for one week to obtain the discharge energy of the battery. The energy density of the battery = discharge energy / battery mass.
[0105] The 25°C cycle number at 80% capacity retention is measured as follows: the battery is subjected to 0.5C charging and discharging cycles at 25°C, and the maximum charging and discharging cycle number at which the battery can maintain 80% capacity is measured.
[0106] Example 2
[0107] The method of Example 1 is followed, except that the proportion of fluoroethylene carbonate in the electrolyte is 15% by weight, and a lithium ion battery is obtained in the same manner. The measurement results and the preparation conditions are shown in Table 1.
[0108] Example 3
[0109] The method of Example 1 is followed, except that the proportion of fluoroethylene carbonate in the electrolyte is 20% by weight, and a lithium ion battery is obtained in the same manner. The measurement results and the preparation conditions are shown in Table 1.
[0110] Example 4
[0111] The method of Example 1 is followed, except that the compaction density of the negative electrode sheet is 1.1 g / cm 3 , and a lithium ion battery is obtained in the same manner. The measurement results and the preparation conditions are shown in Table 1.
[0112] Example 5
[0113] The method of Example 1 is followed, except that the compaction density of the negative electrode sheet is 1.5 g / cm 3 , and a lithium ion battery is obtained in the same manner. The measurement results and the preparation conditions are shown in Table 1.
[0114] Example 6
[0115] The procedure of Example 1 was followed except that the formation temperature was 50°C, and lithium ion batteries were similarly obtained. The results of the measurements and the conditions of the preparation are shown in Table 1.
[0116] Example 7
[0117] The procedure of Example 1 was followed except that the negative active material was the following components in mass percent, and lithium ion batteries were similarly obtained. The results of the measurements and the conditions of the preparation are shown in Table 1.
[0118] Negative active material: micron silicon 90%, 3% graphite, conductive carbon black 0.5%, single-walled carbon nanotube 0.2%, graphene conductive agent 0.05%, butadiene styrene rubber 1%, carboxymethyl cellulose 1.25%, polyacrylic acid-based binder 4%, the compacted density of the negative electrode sheet was 1.3 g / cm 3 , the area density was 30 g / m 2 .
[0119] Example 8
[0120] The procedure of Example 1 was followed except that the negative active material was the following components in mass percent, and lithium ion batteries were similarly obtained. The results of the measurements and the conditions of the preparation are shown in Table 1.
[0121] Negative active material: micron silicon 95%, conductive carbon black 0.5%, single-walled carbon nanotube 0.2%, graphene conductive agent 0.05%, butadiene styrene rubber 1%, carboxymethyl cellulose 1.25%, polyacrylic acid-based binder 2%, the compacted density of the negative electrode sheet was 1.3 g / cm 3 , the area density was 30 g / m 2 .
[0122] Example 9
[0123] The procedure of Example 1 was followed except that the negative active material was the following components in mass percent, and lithium ion batteries were similarly obtained. The results of the measurements and the conditions of the preparation are shown in Table 1.
[0124] Negative active material: micron silicon 80%, 13% graphite, conductive carbon black 0.5%, single-walled carbon nanotube 0.2%, graphene conductive agent 0.05%, butadiene styrene rubber 1%, carboxymethyl cellulose 1.25%, polyacrylic acid-based binder 4%, the compacted density of the negative electrode sheet was 1.3 g / cm 3 , the area density was 30 g / m 2 .
[0125] Comparative Example 1
[0126] The method of Example 1 was followed, except that the proportion of fluoroethylene carbonate in the electrolyte was 5% by weight, and a lithium ion battery was obtained in the same manner. The measurement results and the preparation conditions are shown in Table 1.
[0127] Comparative Example 2
[0128] The method of Example 1 was followed, except that the negative active material was the following components in mass percentage, and a lithium ion battery was obtained in the same manner. The measurement results and the preparation conditions are shown in Table 1.
[0129] The negative active material: micron silicon 75%, 18% graphite, conductive carbon black 0.5%, single-walled carbon nanotubes 0.2%, graphene conductive agent 0.05%, butyl rubber 1%, carboxymethyl cellulose 1.25%, polyacrylic acid binder 4%, the compaction density of the negative electrode sheet was 1.3 g / cm 3 , the area density was 30 g / m 2 .
[0130] Comparative Example 3
[0131] The method of Example 1 was followed, except that the compaction density of the negative electrode sheet was 1.0 g / cm 3 , and a lithium ion battery was obtained in the same manner. The measurement results and the preparation conditions are shown in Table 1.
[0132] Comparative Example 4
[0133] The method of Example 1 was followed, except that the compaction density of the negative electrode sheet was 1.6 g / cm 3 , and a lithium ion battery was obtained in the same manner. The measurement results and the preparation conditions are shown in Table 1.
[0134] Table 1
[0135]
[0136] The above describes the preferred embodiments of the present application in detail, but the present application is not limited thereto. Within the technical concept of the present application, various simple modifications can be made to the technical solutions of the present application, including the combination of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as disclosed by the present application and fall within the protection scope of the present application.
Claims
1. A lithium-ion battery, characterized by, The lithium ion battery comprises a positive electrode, a negative electrode, a separator between the positive electrode and the negative electrode, and a non-aqueous electrolyte, The negative electrode comprises a negative electrode current collector and a negative electrode material, the negative electrode material comprises a negative electrode active material, a first binder and a first conductive agent, the negative electrode active material comprises a micrometer silicon material, and the content of silicon in the negative electrode material is 80% by weight or more, The compacted density of the negative electrode is 1.1-1.7 g / cm 3 , The non-aqueous electrolyte contains a lithium salt and an organic solvent, and the organic solvent contains fluoroethylene carbonate, and the content of the fluoroethylene carbonate in the non-aqueous electrolyte is 10% by weight or more.
2. The lithium-ion battery of claim 1, wherein, The negative electrode active material comprises a micrometer silicon material and graphite; Preferably, the content of silicon in the negative electrode material is 80-95% by weight, the content of graphite is 0-20% by weight, the content of the first binder is 2-6% by weight, and the content of the first conductive agent is 0.05-4% by weight. Preferably, the single-sided areal density of the negative electrode is 20-50 g / m 2 ; Preferably, the first binder is one or more of polyacrylonitrile, polytetrafluoroethylene, sodium carboxymethyl cellulose, styrene butadiene rubber and polyacrylic acid. Preferably, the first conductive agent is one or more of single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene and graphyne.
3. The lithium-ion battery of claim 1, wherein, The positive electrode comprises a positive electrode current collector and a positive electrode material, and the positive electrode material comprises a positive electrode active material, a second binder and a second conductive agent; Preferably, in the positive electrode material, the content of the positive electrode active material is 92-98% by weight, the content of the second binder is 1-4% by weight, and the content of the second conductive agent is 1-4% by weight. Preferably, the single-sided areal density of the positive electrode is 300-400 g / m 2 , and the compacted density of the positive electrode is 3.4-3.8 g / cm 3 . Preferably, the second binder is one or more of polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polydifluoroethylene, an oxirane-containing polymer, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene butadiene rubber, acrylated styrene butadiene rubber, epoxy resin and nylon. Preferably, the second conductive agent is one or more of conductive graphite, acetylene black, conductive carbon black, graphene, carbon fiber, carbon nanotube and ketjen black. Preferably, the positive electrode active material is an 8-series nickel-cobalt-manganese ternary material and / or a 9-series nickel-cobalt-manganese ternary material.
4. The lithium-ion battery of any one of claims 1-3, wherein, The compaction density of the negative electrode is 1.1-1.5 g / cm 3 .
5. The lithium-ion battery of any one of claims 1-3, wherein, The D50 of the micrometer silicon material is 0.5-20 μm.
6. The lithium-ion battery of any one of claims 1-3, wherein, The lithium salt is one or more of LiPF6, LiBF4, LiBOB, LiODFB, LiFSI, LiTFSI and LiPO2F2. Preferably, the organic solvent further contains one or more of ethylene carbonate, methyl ethyl carbonate, diethyl carbonate and dimethyl carbonate. Preferably, the content of the lithium salt in the non-aqueous electrolyte is 1.0-1.5 mol / L.
7. The method of producing a lithium-ion battery according to any one of claims 1 to 6, characterized in that, The method comprises the following steps, 1) After the injection of the battery cell, the battery cell is left to stand, and then the battery cell is vacuumized and sealed; 2) The sealed battery cell is subjected to two-stage charging; 3) The charged battery cell is discharged to 15-25% SOC; 4) The discharged battery cell is vacuumized and sealed again, The two-stage charging includes: a first stage charging of constant current charging to 60-70% SOC at 0.2C current, and a second stage charging of constant current charging to 100% SOC at 0.1C current.
8. The method of claim 7, wherein, The standing condition includes: the standing temperature is 25-40 DEG C, and the standing time is 24-48h.
9. The method of claim 7, wherein, The two-stage charging is carried out at a pressure of 1-2Mpa and a temperature of 40-50 DEG C.
10. The method of any of claims 7-9, wherein, The discharging is carried out at a pressure of 1-2Mpa and a temperature of 40-50 DEG C. The discharging is carried out at a pressure of 1-2Mpa and a temperature of 40-50 DEG C.